Florida Solid and Hazardous Waste Regulation Handbook: Composting - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
The Florida Department of Environmental Protection (DEP) has established detailed regulations for the production and use of compost created from waste. These regulations exclude compost obtained from backyard composting and normal farming operations. Compost from these activities is exempt from regulation only if it is used on the property where it was composted, as part of the farming operation. Any compost that is sold must meet the requirements of the regulations. This is EDIS document FE462, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.